Planning and analysis methods of revenues and expenses by individual activities of railway transport companies - T. M. Rogulenko; A. A. Bondarenko (Управление)
The problems of formation and improvement of accounting and control system in information support of management railway transportation strategy have been analyzed.Implementation of the purpose of the article related to the improvement of the principles and planning and analysis methods of revenues and expenses for certain activities of railway transport companies on the basis of generalization of the theory and best practices of management of complex economic systems, allowed us to develop proposals aimed at optimizing the planning and analysis methods of profits and expenses for certain activities of railway transport companies. In particular, the main tasks of intra-corporate business planning in the presentation of managers, types of generated business plans, their relationship, have been formulated; the conditions that ensure the effectiveness of the business planning system have been defined. Recommendations for operational co-ordinating in the contour of planning processes, improving the methodology of intra-corporate financial and production control have been given. Approaches to the analysis of revenues and expenses for certain types of activities, methods of analysis of deviations of planned indicators from the actual ones have been determined.The composition of the costs of railway transport enterprises and the possibility of using their classification for management purposes have been analyzed. The possibilities of using “direct costing” in railway transport companies have been shown, by providing separate accounting of fixed and variable costs in the context of the most significant cost items in terms of the level of calculation, the formation of the nomenclature of costs directly related to the processes of creating specific products and the volume of activity of the allocated responsibility centers. Recommendations on the sequence of calculating the variable cost of rail transport and financial results, the composition of key indicators for planning, reporting and monitoring of the structural units of railway transport enterprises have been given. It has been proposed to introduce additional analytical columns in the forms of internal reporting of railway companies, which will reflect the absolute and relative deviations of the values of budget indicators.